Brazilian social policy: Outcomes and dilemmas - Milko Matijascic (Institute for Applied Economic Research (ipea), 2019)
Since redemocratization in 1985, Brazil's system of social protection became more focused on the neediest while at the same time emphasizing universal access, especially focusing education and healthcare. In a traditional context of severe inequality, the sub-national units of government played a greater role in reaching the broader population with diverse social policies. Yet, Brazil's social protection model favors cash transfers over social services, and reduces inequalities in the context of a highly unequal labor market. Strategies based on cash transfers policies appear to have reached their limits, because they are not the most effective way to promote equality and generate opportunities, when compared to the outcomes obtained by social service policies provision. Furthermore, while much progress toward reducing inequality has been achieved, benefits and services continue to fall short of what might be considered a welfare state. Poor administrative procedures, institutional problems and reduced efficiency are definitely major challenges to overcome in the Brazilian social policy scene.
Keywords: I00; 330; social policy; development; public policies; Brazil